HIV risk among female sex workers with different patterns of drug use behaviors in Southwest China: a cross-sectional study - Tang, Zhenzhu (AIDS Care, 2014)
Although many researchers found that drug use behaviors significantly increased HIV risk, few of them investigated the association between HIV risk and different drug use behaviors among female sex workers (FSW) in China. The current study examines demographic and behavioral risk factors as well as the infections of HIV, syphilis and HCV among a subgroup of FSW who are injection drug users (IDU) or non-injection drug users (NIDU) in comparison to non-drug users (non-DU). We conducted secondary analysis of the 2010 National Sentinel Surveillance (NSS) data from Guangxi China. A self-administered, standard behavioral surveillance survey was completed by a total of 12,622 FSW recruited from Guangxi, China. The Guangxi 2010 NSS sample included 2.6% NIDU and 0.5% IDU. Compared to non-DU, IDU were more likely to report no condom use in the last sex act (aOR=3.25, 95%CI=1.65, 6.40), inconsistent condom use in the past month (aOR=4.88, 95%CI=2.66, 8.96), having an HIV testing (aOR=2.48, 95%CI=1.34, 4.58), infections of HIV (aOR=42.60, 95%CI=9.45, 192.06), syphilis (aOR=4.13, 95%CI=1.86, 9.16), and HCV (aOR=74.54, 95%CI=30.26, 183.61). NIDU had 2.89 times higher than non-drug users to report a history of STD and 26% less likely to report inconsistent condom use in the past month (p<0.05). We called for tailored, accessible and non-judgmental drug treatments coupled with effective sexual risk reduction interventions to help FSW with various drug use problems to reduce their vulnerability and susceptibility of HIV risk in China as well as other cultural settings.